The nature of the post-translational modifications of the autoantigen LL37 influences the autoreactive T-helper cell phenotype in psoriasis - Lande, Roberto; Mennella, Anna; Palazzo, Raffaella; Favaro, Rebecca; Facheris, Paola; Mancini, Flavia; Ocone, Giuseppe; Botti, Elisabetta; Falchi, Mario; Pietraforte, Immacolata; Conrad, Curdin; Bianchi, Luca; et al. (Frontiers in Immunology, 2025)
Psoriasis is a chronic skin disease evolving to psoriatic arthritis (PsA) in 30% of cases. LL37 is a psoriasis T-cell autoantigen and, in complex with self-DNA/RNA, a trigger of type I interferon (IFN-I) and pro-inflammatory factors in dendritic cells. LL37 can undergo irreversible post-translational modifications (PTMs), namely, citrullination and carbamylation, which are linked to a neutrophil-dominated inflammation. Notably, in PsA, carbamylated and citrullinated LL37 (carb-LL37 and cit-LL37) become antibody targets. Here, we analyze the presence of, and the T-cell and antibody reactivity to, cit-LL37 and carb-LL37, to address the occurrence and significance of these PTMs in psoriasis. The presence of modified LL37 in skin biopsies was assessed by laser scanner confocal microscopy (LSCM); T-cell responses to modified LL37 were assessed by Ki67 assay and intracellular cytokine staining using flow cytometry; serum autoantibodies to the same antigens were tested by enzyme-linked immunosorbent assay (ELISA). The results show that native and modified LL37 (both carb-LL37 and cit-LL37) are detectable in psoriatic skin, but not in healthy donors’ (HD) skin, where they colocalize with neutrophil infiltrates and neutrophil extracellular trap formation (NETosis). Psoriatic T cells and antibodies recognize native LL37, cit-LL37, and carb-LL37, but only CD4-T-cell responses to native LL37 and carb-LL37 correlate with psoriasis area severity index (PASI), whereas CD8-T-cell responses to the same peptides correlate with PASI in the HLA-Cw6*02-positive subgroup. CD4-T cells specific for modified LL37 express heterogeneous T-helper (Th) phenotypes: native/carb-LL37-specific T cells mainly manifest a Th1/Th17-like phenotype, whereas cit-LL37-specific T cells resemble Th-follicular (Thf)-like cells. In vitro T-cell polarization experiments suggest that distinct pro-inflammatory effects of LL37 and modified LL37, in complex with self-nucleic acids, may concur to these phenomena. This is the first evidence in psoriasis that PTMs of an autoantigen with innate immune cell stimulatory ability dictate autoreactive Th-cell polarization. These data, obtained using LL37 as a model autoantigen, indicate that citrullination and carbamylation pathways may play a role in the psoriasis course, generating epitopes to which immunological tolerance does not exist and potentially concur to PsA development.